Teacher's Use of WhatsApp Application to Solve Elementary School Students' Online Learning Difficulties - Eko Kuntarto; Faizal Chan; Nurul Qalbi Eka Pratiwi (Profesi Pendidikan Dasar, 2021)
This research aims to describe the types of difficulties encountered by students when conducting online learning through WhatsApp, as well as how teachers address students' learning difficulties. The method used in this research was qualitative research method using case study design. Data were gathered through online observation and interviews. Data analysis was carried out by collecting data, analyzing data, and drawing conclusions. To check the validity of the data, sources and technique triangulations were used. The results of this research showed that there were several difficulties experienced by the students during online learning through WhatsApp group, such as lack of support facilities because students did not have their own mobile phones, unstable internet network, and insufficient internet quota. Regarding the use of WhatsApp in learning activities, students had difficulty discussing in the group or using WhatsApp features. The teacher overcame the obstacles for students who did not have their own mobile phones by asking their classmates or neighbors who lived nearby to provide information related to learning activities. To address challenges such as an unstable internet network, the teacher instructed students to find a location with a good network while learning. Then, regarding students who did not have an internet quota, the teacher recorded the student's WhatsApp numbers so they could get free internet assistance from the Ministry of Education and Culture. To solve problems related to the difficulty of students discussing in groups and difficulties using the WhatsApp feature, the teacher always guided and assisted students on how to use the WhatsApp features in the learning process.